Enhancing The Role Of Government Internal Supervisory Apparatus (APIP) In Corruption Prevention: A Case Study Of Halmahera Selatan Regency - Abd. Wahab, Muhammad Zaki; Malik, Faissal; Rumkel, Nam (Jurnal Hukum Volkgeist, 2024)
Corruption significantly threatens state financial stability and governance integrity. This study explores optimizing the role of the Government Internal Supervisory Apparatus (Aparatur Pengawasan Intern Pemerintah, APIP) in preventing corruption in Halmahera Selatan Regency. It aims to analyze APIP’s effectiveness and identify challenges in fulfilling its supervisory role. A combined juridical-normative and juridical-empirical approach was applied. The juridical-normative method analyzed legal frameworks, including laws and policies regulating APIP’s role. The juridical-empirical approach involved primary data collection through interviews with APIP officials and regional government representatives, complemented by secondary data from literature and case studies. Qualitative analysis was conducted to identify key patterns and insights. Findings indicate that APIP’s role in corruption prevention is limited by weak institutional independence, inadequate budget allocation, and low human resource competency. These constraints reduce its ability to perform effective oversight. The study recommends institutional reforms to strengthen APIP’s independence, increase budget allocations, and provide continuous training for personnel. These measures are crucial for effective corruption prevention and fostering transparent and accountable governance at the regional level.